2013
DOI: 10.1590/s0034-89102013000700006
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de alimentos fora do domicílio no Brasil

Abstract: OBJECTIVE:To describe foods consumed away from home and associated factors in Brazil. METHODS:The study was based on the National Dietary Survey which was conducted among residents aged over 10 years old in 24% of households participating in the Household Budget Survey in 2008-2009 (n = 34,003). The consumption of food and beverages was collected through records of foods consumed, type of preparation, quantity, time and food source (inside or outside home). The frequency with which individuals consumed food aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
62

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 22 publications
3
40
0
62
Order By: Relevance
“…Além disso, os registros foram detalhadamente revisados junto aos participantes por nutricionistas treinados. Nesse momento, as anotações que davam margem a dúvidas eram esclarecidas, e os participantes eram sondados para completar as informações sobre alimentos usualmente omitidos em inqué-ritos alimentares e longos períodos sem relato de consumo alimentar 38 .…”
Section: Resultsunclassified
“…Além disso, os registros foram detalhadamente revisados junto aos participantes por nutricionistas treinados. Nesse momento, as anotações que davam margem a dúvidas eram esclarecidas, e os participantes eram sondados para completar as informações sobre alimentos usualmente omitidos em inqué-ritos alimentares e longos períodos sem relato de consumo alimentar 38 .…”
Section: Resultsunclassified
“…In Brazil studies that evaluated diet quality using the HEI or BHEI-R have found worse eating habits in adolescents 22,23 and adult females 24 . The fact that females have better diet quality could be the result of several factors, such as increased attention to health and signs of disease, increased concern with body image, the role of being the family caregiver and generally having the responsibility of selecting and preparing meals, as well as the lower consumption of food away from home 25,26 ; women also have more careful attitude towards their health than men 27,28 . The increase in diet quality scores with advancing age has also been observed by other authors 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Industrialized, ultra-processed foods consumed outside the households and snacks are high calorie-dense foods, with high total fat, saturated and trans fats, simple carbohydrates and sodium, and low fiber concentration. Adolescents show the highest rate of consumption of foods outside the house and greater average consumption of cakes and cookies, industrialized salty snacks, milk and dairy products, sweets, soft drinks, juice, fried foods and sandwiches (32). These foods are among the ten more consumed by adolescents in Brazil (33).…”
Section: Discussionmentioning
confidence: 99%